Quale didattica per il plurilinguismo oggi? - Benucci, Antonella (Educazione Linguistica Language Education, 2020)
The contribution addresses the complex problem of multilingual language development in learning paths in L2 aimed at adult subjects to facilitate social integration, ultimate goal which is not reachable without the more functional aim of a methodological elaboration of educational paths that are adequately inclusive and respectful of diversity and otherness. The underlying concept is that inclusive education is a tool to combat discrimination if it makes use of adequate practices for the enhancement of the individual, respecting his/her life experience.